PEMBUATAN MEDIA PEMBELAJARAN DENGAN BANTUAN APLIKASI OODLÜ - Onyx Nifty; Herlina Jasa Putri Harahap (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The objective of this study is to develop an Oodlü-based learning medium for the Lesen A1 course on the topic “Alltag und Familie”. This study employs a qualitative approach using the development model proposed by Richey and Klein. The model consists of three phases: (1) Planning, (2) Development, and (3) Evaluation. The data source for this study is the textbook Netzwerk neu A1 by Stefanie Dengler et al. (2019). The data consist of reading texts, vocabulary, and exercises related to the topic “Alltag und Familie”, covering the three subtopics: Tagesablauf (Daily Routine), Uhrzeiten (Time), and Familie (Family). The learning medium was developed on the Oodlü platform in the form of interactive exercises using the question types Multi-Word Text, True/False, and Click the Letters to Spell the Word. These exercises were integrated with the games Archery, Bubble Breakout, and Cow Cakes. The results of this study are an Oodlü-based learning medium consisting of a total of 45 interactive questions for the Lesen A1 course on the topic “Alltag und Familie”. The learning materials were validated by a material expert based on five evaluation criteria and received a score of 95.8, which falls into the “very good” category. In addition, the learning medium was validated by a media expert based on nine evaluation criteria and obtained a score of 97.2, which is also categorized as “very good.” Based on these findings, it can be concluded that the developed learning medium is suitable for use as a supplementary instructional medium in German language teaching for the Lesen A1 course on the topic “Alltag und Familie.”